Branderpreneurship Framing Analysis of MSME Brand "Daviena Skincare" - Riska Yuliarosa; Bambang Sukma Wijaya (International Journal of Entrepreneurship, Business, and Creative Economy, 2024)
Few MSME skincare and cosmetics brands focus on developing brand value to build their business. Among them is Daviena Skincare in Indonesia. This article examines Daviena's entrepreneurship-based brand development strategy using the Branderpreneurship Framing Analysis (BFA) methodology approach. BFA systematically traces and details the value development strategy according to the elements in BrandCoVD (Branderpreneurship's Circle of Values Development), namely identifying, creating, delivering, communicating, maintaining, evaluating, and renewing values. The analysis shows that as a startup that cannot afford influencers and celebrities like other skincare brands, Daviena Skincare utilizes social media with self-demo techniques by the owner and models to convince consumers of the unique advantages of its products. This communication technique provides a domino effect for consumer users to express their experiences through organic testimonials. This study can inspire other MSME and startup brands to develop their brand value with limited resources.